Penyerapan Zat Warna Tekstil BR Red HE 7B Oleh Jerami Padi - Saepudin Suwarsa (Jurnal Matematika & Sains, 1998)
The straw in a agricultural wastes which is accumulated in a large quantity but still not much utilized, a part of it was burned and the other is used in a small part as an animals feed. At present, in Indonesia textile industries are so developed such that dyestuff and other colouring substances were very much used in the process especially in the dying process. Part of them was discarded as a wasteÂ  and becomes a pollutant, when it is discharged to the river in the environment. The straw have been investigated in a way that it can adsorb the dyestuff. Straw was first heated in 2% sodium hydroxide solution prior to usage followed by washing with water to neutral. The optimum adsorption was then determined. In the 0,1 M hydrochloric acid condition 1 gram of the straw adsorbed 9,8 mg of BR Red HE 7B dyes.